Enhancing Properties of Metakaolin-Based Geopolymers: The Effect of Zirconia and Silica Nanosphere Additions - Firdaus, Mevy; Harmaji, Andrie; Febrina, Eva; Ruth, Imelda; Sunendar, Bambang; Suryatmojo, Ibnu (Physics and Chemistry of Solid State, 2026)
Geopolymers are known for its high compressive but low tensile strength due to its brittle nature, which restricts the use of geopolymers as structural material. It is important to enhance their mechanical performance by incorporating reinforcing materials. This research examines the contribution of silica nanospheres and zirconia to enhance the tensile strength of geopolymer composites utilizing metakaolin. Geopolymers were prepared from an 8M NaOH and sodium silicate activator, which was prepared for 24 hours prior to mixing in a ratio of 2:1. Confirmation of the amorphous silica presence, monoclinic and tetragonal zirconia, and crystalline phases in metakaolin including quartz, mullite, and hematite was verified using X-ray diffraction (XRD) analysis. The scanning electron microscope (SEM) showed that both silica nanospheres and zirconia resulted in a more densely packed microcomposite material with less porosity. Diametral tensile strength (DTS) at 28 days was seen to improve from 2.24 MPa (control) to 2.58 MPa with 80% silica and 3.61 MPa with 60% zirconia and 20% silica nanospheres. These improvements showed that nanomaterials such as silica can enhance the densification of the matrix while zirconia contributes structural reinforcement for improved mechanical properties. The findings here are consistent with earlier work that demonstrated the synergistic effects of silica nanospheres and zirconia to improve geopolymers performance. Findings from this study further demonstrates modified geopolymers can be used in applications requiring high mechanical strength but would require additional investigation to determine its durability and thermal properties to use them in structural and functional applications.